Dinamika Kehidupan Nelayan Pangandaran (1950-1970 an) - Afidah, Dahimatul (Siginjai: Jurnal Sejarah, 2022)
Pangandaran is one of the areas where the community's economy relies on the maritime sector. The life dynamics of Pangandaran fishermen from 1950 to 1970 showed an important change. These changes include changes in the use of equipment for sailing to changes in economic characteristics. From 1950 to the end of 1960, the Pangandaran community still used traditional equipment for sailing. Changes occurred in 1970 when the government began to introduce a more modern shipping system using engines. In addition to shipping techniques, major changes also occurred which also began in the 1970s when Pangandaran was opened to become a tourist attraction open to the public. This change can be seen from the change in the economic mindset of the people who used to be "farmer fishermen" then turned into "trade fishermen". This study uses historical research methods consisting of heuristics, verification, interpretation and historiography. This study tries to combine two main sources, namely archival sources and oral sources where the research data sources are obtained from interviews with historical actors. The results of this study are expected to enrich the sources of maritime history studies which are still quite limited.